Adverse drug reactions. Issue 4 (April 2017) - Charlton, Matthew; Thompson, Jonathan
Abstract: Adverse drug reactions (ADRs) are a common and important cause of morbidity and mortality. They occur frequently in patients undergoing anaesthesia or in Intensive Care. ADRs occur by a number of mechanisms, some of which remain unclear, but several risk factors have been identified. It is increasingly recognized that pharmacogenetic factors are important in determining susceptibility to ADRs. Medical practitioners should be aware of their responsibility to report ADRs and know how to report them.